2018
DOI: 10.1016/j.jgar.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of a CTX-M-11-encoding and quinolone-non-susceptible Klebsiella pneumoniae ST194 isolate from a hospitalised dog in Greece

Abstract: To the best of our knowledge, this is the first detection of a CTX-M-11-producing K. pneumoniae isolated from a canine. The whole genome sequence of the isolate has been deposited at GenBank to serve as a future reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Furthermore, Puncharat et al (2015) revealed that ESBL-producing E. coli and K. pneumoniae had less than 50% susceptibility to Gentamicin which was in agreement to our result. Those bacteria are in the same family, Enterobacteriaceae, containing plasmids harbored different resistance genes resulting in the horizontal gene transfer of antimicrobial resistance (Pornsukarom and Thakur, 2017;Chatzopoulou et al, 2018). When considering Table 3, all K. pneumoniae isolates in this study had trend to MDR which can be caused global public health problem.…”
Section: Predominant R-patternsmentioning
confidence: 83%
“…Furthermore, Puncharat et al (2015) revealed that ESBL-producing E. coli and K. pneumoniae had less than 50% susceptibility to Gentamicin which was in agreement to our result. Those bacteria are in the same family, Enterobacteriaceae, containing plasmids harbored different resistance genes resulting in the horizontal gene transfer of antimicrobial resistance (Pornsukarom and Thakur, 2017;Chatzopoulou et al, 2018). When considering Table 3, all K. pneumoniae isolates in this study had trend to MDR which can be caused global public health problem.…”
Section: Predominant R-patternsmentioning
confidence: 83%